Who Wins? Evaluating the Impact of UK Public Sector Pension Scheme Reforms - Alexander M. Danzer; Peter Dolton; Chiara Rosazza Bondibene (Institute for the Study of Labor (IZA), 2016)
Radical changes have been implemented to pension schemes across the UK public sector from April 2015. This paper simulates how these changes will affect the lifetime pension and how the negotiated pension changes compare across six public sector schemes by level of education. Specifically, we simulate the occupation specific Defined Benefit (DB) pension wealth accumulated for a representative employee over the lifecycle by factoring in the recent changes to pension conditions. We find that less educated workers with low or moderate earnings in the NHS, Local Government and Civil Service schemes are the winners having secured an increase in the value of their pension of between 10-20%. Graduate workers with faster wage growth in the Civil Service, Teachers and Local Government schemes loose between 3% and 5%. This is in sharp contrast with the Police and Fire forces who have lost around 40% irrespective of their education.
Keywords: J32; H55; J45; 330; defined benefit; public sector; pension reforms